Reconstruction of Islamic Value-Based Islamic Education Learning Evaluation in the Independent Curriculum - Mohammad Madani; Mohammad Iqbal Ujari (UIN Mataram, 2026)
The evaluation of PAI learning is still oriented to the cognitive side, while the affective, spiritual, and character aspects are still not fully well reached. This research aims to reconstruct the evaluation of Islamic Religious Education (PAI) learning in the Independent Curriculum through the integration of Islamic values as the basis for assessment. This research uses a qualitative approach with a type of research called library research. The data obtained will be analyzed using content analysis techniques on various writings related to learning assessment, Islamic education, and Independent Curriculum assessment. This research produced a PAI evaluation reconstruction model that integrates the values of ṣidq, amanah, 'adl, mas'uliyyah, and ihsan into all stages of assessment, including diagnostic, formative, summative assessment, and learning follow-up. The model offered places amanah as the basis for diagnostic assessment, ihsan for formative assessment, 'adl for summative assessment, mas'uliyyah for evaluation follow-up, and ṣidq as a value that animates the entire assessment process. These findings show the formation of an evaluation framework that is comprehensive, humanist, and sustainable. Within this framework, evaluation is not solely directed at assessing students' academic achievements, but also plays a role in developing their character and strengthening their spiritual dimension.